Unidad didáctica: guía para la enseñanza de juegos expresivos con niños de educación primaria - Cely Moreno, Angie Daniela; Ortiz Castiblanco, Vanessa Valentina (Universidad Antonio Nariño, 2021)
The primer "Guide for the teaching of games and exploration with materials for primary school children" is based on the creation and systematization of the activities proposed during the years 2019-2 - 2020-2 with the courses, transition, first, third and fourth proposals in the pedagogical practice carried out in the Paulo VI educational institution, becomes a pedagogical material between the reflection of how we produce certain themes and adaptation of each of the activities taking them to an artistic context, where children can develop and enhance their cognitive and basic skills such as: jumping, throwing, catching, imagining, creating, among others, this material is the combination of three categories, which are: games and exploration with materials and virtual education.